Medial Radial Head Dislocation Associated with a Proximal Olecranon Fracture: A Bado Type V? - Neil Segaren; Hani B. Abdul-Jabar; Nicholas Segaren; Matthew Barry (Case Reports in Surgery)
The Monteggia fracture is relatively rare. We present an unreported configuration of a traumatic olecranon fracture with a concomitant medial radial head dislocation in a 3-year-old male. This injury was initially missed and required a subsequent operative intervention. Following surgery, there was evident fracture union, articular congruency, and a full functional recovery. Medial radial head dislocation is not accounted for in the Bado (1967) classification of the Monteggia lesion and hence we propose the addition of a Bado V category.